Planetary period oscillations in Saturn's magnetosphere: Comparison of magnetic oscillations and SKR modulations in the postequinox interval. Issue 9 (22nd September 2014) - Provan, G.; Lamy, L.; Cowley, S. W. H.; Dougherty, M. K.
Abstract We compare the properties of planetary period oscillations observed in Saturn kilometric radiation (SKR) and magnetospheric magnetic field data from Saturn equinox in August 2009 to July 2013. As shown previously, the southern and northern oscillation periods converged across equinox from 10.8 h and 10.6 h, respectively, during southern summer, to closely common values 10.7 h approximately 1 year after equinox. Near coalescence is judged to have occurred approximately 3 months earlier in the SKR data, centered in late June 2010, than in the magnetic data, in late September, though SKR periods were particularly difficult to determine during this interval due to less clearly modulated emissions. Both data sets agree, however, that by early November 2010 the two periods had separated again but remained closely spaced with a difference in period of 3 min about a mean of 10.67 h, with the southern period remaining longer than the northern. Thus, no enduring reversal of the northern and southern periods took place following near coalescence in mid‐2010, the periods remaining uncrossed to the end of the interval studied here. The SKR modulations also show effects related to the sharp amplitude changes observed in the magnetic oscillation data at 100–200 day intervals since February 2011, though the correspondences are not exact, indicating that other factors such as "seeing" effects on the variable Cassini orbit are also involved. Postequinox variations in the relative phase between the magnetic and SKR oscillations are also shown to be related to changes in orbit apoapsis orientation.